Improving nutrition in Bihar: Insights from examining trends in outcomes, determinants and interventions between 2006 and 2016 - George, Nitya Rachel; Avula, Rasmi; Nguyen, Phuong Hong; Tran, Lan Mai; Menon, Purnima (International Food Policy Research Institute, 2017)
The purpose of this Policy Note is to examine the trends in undernutrition in Bihar and to document trends and geographic variability in the major determinants of nutrition and the coverage of key nutrition and health interventions. In doing this analysis, we aim to highlight key areas for actions to improve nutrition in Bihar.